SIFD-associated TRNT1 deficiency unveils importance of TSPO during macrophage antibacterial and antiviral responses - Ahmed, Duale; Slade, Angelo; Fatica, Thet; Baird, Stephen; Bhattarai, Krishna; Atallah, Thérèse; Cassol, Edana; Holcik, Martin (Frontiers in Immunology, 2025)
IntroductionMitochondria support cellular biosynthetic and bioenergetic demands and mediate cell signaling. Their dysfunction is implicated in a wide range of diseases, including congenital disorders. One such disorder, sideroblastic anemia with B-cell immunodeficiency, periodic fevers, and developmental delay (SIFD), is caused by mutations in the tRNA-nucleotidyltransferase enzyme TRNT1. While SIFD is known to affect immune function, the role of macrophages—key mediators between innate and adaptive immunity—remains underexplored.MethodsTo investigate the impact of TRNT1 deficiency on macrophage function, we employed siRNA-mediated knockdown of TRNT1 in murine RAW264.7 macrophages. Cells were stimulated with lipopolysaccharide (LPS) and Polyinosinic:polycytidylic acid (Poly (I:C)) to mimic bacterial and viral infections, respectively. Cytokine production was measured, and mitochondrial reprogramming was assessed. Bioinformatic analysis was conducted to identify TRNT1-dependent transcripts, focusing on mitochondrial-associated proteins. Functional rescue experiments were performed using TSPO ligands and TSPO overexpression.ResultsTRNT1 knockdown impaired inflammatory cytokine production in response to both LPS and Poly (I:C). This correlated with diminished mitochondrial reprogramming, suggesting a mechanistic link between TRNT1 activity and macrophage effector function. Transcriptomic analysis identified the mitochondrial translocator protein (TSPO) as a TRNT1-dependent gene. TSPO expression was differentially regulated following stimulation in TRNT1-deficient cells. While TSPO ligand activation failed to restore cytokine production, TSPO overexpression prior to TRNT1 knockdown selectively rescued the inflammatory response to Poly (I:C), but not LPS. This rescue was associated with enhanced recruitment of VDAC to the mitochondrial permeability transition pore via TSPO.DiscussionOur findings reveal that TRNT1 is critical for pathogen-specific mitochondrial reprogramming in macrophages, influencing their inflammatory capacity. The differential restoration of cytokine responses via TSPO overexpression underscores the complexity of mitochondrial signaling in immune regulation. These insights suggest that targeting mitochondrial pathways may offer a novel therapeutic strategy for managing immunodeficiency in SIFD.